2012
DOI: 10.3945/ajcn.111.026708
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of gluten-free diet compliance in celiac patients by assessment of gliadin 33-mer equivalent epitopes in feces

Abstract: Background: Certain immunotoxic peptides from gluten are resistant to gastrointestinal digestion and can interact with celiac-patient factors to trigger an immunologic response. A gluten-free diet (GFD) is the only effective treatment for celiac disease (CD), and its compliance should be monitored to avoid cumulative damage. However, practical methods to monitor diet compliance and to detect the origin of an outbreak of celiac clinical symptoms are not available.Objective: We assessed the capacity to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
147
0
17

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 22 publications
9
147
0
17
Order By: Relevance
“…The HMW and LMW glutenin subunits were observed as bands ranging from 75 to 110 kDa and 40 to 45 kDa, respectively, which was consistent with the findings of Battais et al (2003). Bands in the gliadin subunits ranged from 50 to 67 kDa (omega-gliadin) and 33 to 45 kDa (alpha-, beta-, and gamma-gliadin) (Comino et al, 2012). In this study, omega-gliadin was observed around 63 kDa (Fig.…”
supporting
confidence: 79%
“…The HMW and LMW glutenin subunits were observed as bands ranging from 75 to 110 kDa and 40 to 45 kDa, respectively, which was consistent with the findings of Battais et al (2003). Bands in the gliadin subunits ranged from 50 to 67 kDa (omega-gliadin) and 33 to 45 kDa (alpha-, beta-, and gamma-gliadin) (Comino et al, 2012). In this study, omega-gliadin was observed around 63 kDa (Fig.…”
supporting
confidence: 79%
“…The size of gliadins is between 33 and 67 kDa and that of glutenins is between 75 and 110 kDa (Battais et al 2003;Kim et al 2016). Among gliadins, the size of omega-5 gliadin, which is a major inducer of WDEIA, is between 50 and 67 kDa (Comino et al 2012). By considering the characteristics of wheat proteins, we suggest that crude antigens extracted with PBS mostly include salt-soluble proteins; that is, non-gluten proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The benefit of a gluten-free diet have all patients with celiac disease, regardless of degree of enteropathy [37]. Adherence to a gluten-free diet may be measured using a special questionnaire [35] or by measuring 33-mer gliadin epitope in the stool [33,34]. Clinical symptoms may persist even after the deployment of a gluten-free diet [38], the first measure is necessary to carefully examine adherence to diet.…”
Section: Gluten Free Diet and Its Consequences Celiac Disease And Glmentioning
confidence: 99%